Conceptualizing a Knowledge-based Urban Planning Framework for Tehran Metropolis - Asrin Mahmoudpour; Zohreh A. Daneshpour (صفه)
Conceptualizing a Knowledge-based Urban Planning Framework for Tehran Metropolis Spatial planning is subject to continuous and drastic changes caused by the transition from industrial to information age, globalization and rapid progress in information and communication technology. This requires a paradigm shift from the simplified, mostly linear, Modern planning approach to a complex system-oriented knowledge-based approach. Considering the shortcomings of the current conventional planning practices in Tehran Metropolis, there is an urgent need for establishing a knowledge-based planning framework with its respective principles. This paper attempts to identify the nature and preconditions for knowledge-based urban planning and development, while assessing obstacles in establishing this planning in Tehran. To this end, the theoretical bases of knowledge-based planning are first reviewed. Secondly, the current planning system in Tehran and obstacles for introducing knowledge-based planning within in this system are analyzed using an analytical framework. Two sources of data have been explored: planning documents and semi-structured interviews with key decision-makers in Tehran. The results indicate that the prerequisites for introducing knowledge-based planning in Tehran include: (i) supportive legal instruments; (ii) mechanisms for closer collaboration between planners and decision-makers; (iii) integrated policy framework to coordinate planning at city level; and (iv) a knowledge-based planning conceptual framework adopted as the basis for decision-making.